The Gulf Stream Dynamics Experiment. Inverted Echo Sounder Data Report for the April 1983 to June 1984 Deployment Period. - Tracey,Karen L; Watts,D Randolph (1986)
The Gulf Stream Dynamics Experiment was conducted in the region just northeast of Cape Hatteras from September 1983 to May 1985 to study the propagation and growth characteristics of Gulf Stream meanders. Data collected as part of the field experiment included inverted echo sounders, current meter moorings, and AXBT survey flights. This report documents the inverted echo sounder data collected from September 1983 to June 1984, as well as additional measurements made from April to September 1983. Time series plots of the half-hourly travel time and low-pass filtered thermocline depth measurements are presented for twenty-two instruments. Bottom pressure and temperature, measured at seven of the sites, are also plotted. Basic statistics are given for all the data records shown. Maps of the thermocline depth field in a 240 km by 460 km region are presented at daily intervals. See also AD-A170 758.